An Orderly Mess - Mickūnaitė, Giedrė (Book collections on Project MUSE., 2006)
How does a ruler become "the Great"? Is greatness a part of authority exercised or a part of an image created? These and other questions are addressed in this volume on the life and memory of Grand Duke Vytautas of Lithuania (r.1392-1430). The study raises a hypothesis that Vytautas was the main engineer of his image as the great ruler while his contemporaries and later generations developed this image and adapted it to their needs and understandings. Investigating the propaganda surrounding the grand duke, this study reveals that, in fact, there were two opposite images: that of a good ruler and that of a tyrant. The paradox is that frequently these opposites were based on the same features of the grand duke's character or episodes from his biography. The research is based on a wide array of written and visual sources as well as on records of oral tradition